Monilethrix - Case report of a rare disease - Tasleem Arif; Imran Majid; Mir Laieq Ishtiyaq Haji; Nuzhat Samoon (Our Dermatology Online, 2015)
Monilethrix is a rare genetic disorder of hair characterized by beaded appearance of the hair shaft leading to hair fragility and patchy dystrophic alopecia. In this disorder, the hair shaft has alternate widenings (nodes) and constrictions (internodes) that lead to fracture of hair shaft and varying degree of alopecia. We report an eight year old Kashmiri boy who presented with diffuse hair loss since infancy. As monilethrix is a rare disease entity which prompted us to report this case.